HDL Cholesterol and Functional Scale Measured by the NIHSS in Acute Thrombotic Stroke Patients - Rahayu Nofita Sari; Hanik Badriyah Hidayati; Jusak Nugraha (Universitas Airlangga, 2023)
Highlight: Stroke is one of the leading causes of death and disability in the world. There is correlation between HDL cholesterol in acute thrombotic patients and the functional degree of the NIHSS. The lower rate of HDL cholesterol is related to the higher NIHSS score or the higher level of stroke severity. ABSTRACT Introduction: Stroke is one of the world’s leading causes of death and disability. Acute thrombotic stroke accounts for 87% of all stroke cases. The study of the correlation between high-density lipoprotein (HDL) cholesterol levels and acute thrombotic stroke is still limited, especially on the relationship between HDL levels and the degree of functional stroke. Objective: This study aimed to prove a correlation between HDL cholesterol and the functional scale measured by the NIHSS (National Institutes of Health Stroke Scale) in acute thrombotic stroke. Methods: The design study was cross-sectional, with sampling by consecutive admission based on inclusion and exclusion criteria in the neurological ward (Seruni A) at Dr.Soetomo General Academic Hospital, Surabaya. The NIHSS was used to determine the degree of functional scale, and HDL levels were measured by enzymatic endpoint methods. Results: From the 40 subjects studied, 16 (40%) had normal HDL levels of ≥ 40 mg/dL with an NIHSS score between 0–10, and 24 (60%) had lower HDL levels of ≤ 40 mg/dL with an NUHSS score between 0–20. There were significant results in this study (r = 0.391 and p = 0.013). Conclusion: There was a negative correlation between HDL cholesterol levels and the functional scale measured by the NIHSS in acute thrombotic stroke patients.